Digital literacy and gender in Islamic religious education: Challenges and opportunities in the Indonesian context - Ridha Aulia; Dwi Kurnianingrum; Monica Sundawati Susanto; Heni Hurhaeni; Hardika Ajeng Hapsari (Digital Theory, Culture & Society, 2026)
The advancement of digital technology has transformed how Islamic knowledge is accessed, studied, and disseminated within Islamic Religious Education (PAI) in Indonesia. While these developments create new pedagogical opportunities, they also raise gender-related issues concerning access, participation, moral control, and women’s authority in digital spaces. This study examines the relationship between digital literacy, gender, and Islamic Religious Education (PAI), positioning women as both learners and educators. Using a library research approach, it reviews scholarly literature on digital literacy, Islamic education, gender, and digital learning, focusing primarily on Indonesia while drawing on selected global scholarship for conceptual support. A critical gender-sensitive perspective is employed to analyze digital literacy not merely as a technical skill but as a form of critical religious competence. The findings indicate that digital literacy in PAI encompasses the ability to evaluate Islamic information, identify authoritative sources, practice digital ethics, and interpret religion contextually. Although digital spaces can expand women’s access, participation, and authority, they also reproduce social surveillance and gender-based restrictions. Therefore, PAI should foster digital literacy that is critical, ethical, inclusive, and gender-sensitive, particularly in formal educational settings such as schools and madrasahs.